Strategi Pengelolaan Kedisiplinan Peserta Didik dalam Perspektif Manajemen Pendidikan Islam (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to examine strategies for managing student discipline from the perspective of Islamic educational management. The research problem arises from the low level of student discipline, which is not only reflected in violations of formal rules but also in the lack of internal awareness in fulfilling academic and moral responsibilities. This study employs a qualitative approach using a literature review method by analyzing various relevant scholarly sources. The findings indicate that discipline in Islamic education is a value-based construct rooted in spiritual awareness and moral responsibility, rather than mere compliance with external regulations. The characteristics of student discipline in the modern era tend to be situational, flexible, and influenced by technological developments and social environments. Therefore, discipline management cannot rely on conventional approaches but must be adaptive and value-oriented. From the perspective of Islamic educational management, discipline management strategies should be grounded in the principles of tawhid, amanah, justice, role modeling, habituation, participation, and continuous evaluation. The integration of Islamic values with contextual management approaches is essential in fostering sustainable discipline and shaping students’ character. Keywords: student discipline, Islamic educational management, management strategies, character education, value internalization